Drug repurposing as an alternative for the treatment of recalcitrant bacterial infections - Rangel-Vega, Adrian; Bernstein, Lawrence R.; Mandujano Tinoco, Edna-Ayerim; García-Contreras, Silvia-Julieta; García-Contreras, Rodolfo (Frontiers in Microbiology, 2015)
Bacterial infections remain one of the leading causes of death worldwide, and the therapeutic outlook for these infections is worsening, due the rise of antibiotic resistant strains. The pharmaceutical industry has produced few new types of antibiotics in more than a decade. Researchers are taking several approaches towards developing new classes of antibiotics, including (1) focusing on new targets and processes, such as bacterial cell-cell communication that upregulates virulence; (2) designing inhibitors of bacterial resistance, such as blockers of multi-drug efflux pumps; and (3) using alternative antimicrobials such as bacteriophages. In addition, the strategy of finding new uses for existing drugs is beginning to produce results: antibacterial properties have been discovered in existing anticancer, antifungal, anthelmintic, and anti-inflammatory drugs. In this work we discuss the antimicrobial properties of gallium based compounds, 5-fluorouracil, ciclopirox, diflunisal, and some other FDA-approved drugs.